Regional Economic Outlook, October 2018, Sub-Saharan Africa : Capital Flows and The Future of Work. (Regional Economic Outlook, 2018)
The macroeconomic outlook for sub-Saharan Africa continues to strengthen. Growth is expected to increase from 2.7 percent in 2017 to 3.1 percent in 2018, reflecting domestic policy adjustments and a supportive external environment, including continued steady growth in the global economy, higher commodity prices, and accommodative external financing conditions. Inflation is abating; and fiscal imbalances are being contained in many countries. Over the medium term, and on current policies, growth is expected to accelerate to about 4 percent, too low to create the number of jobs needed to absorb anticipated new entrants into labor markets.